Effects of antiplatelet agents on pulmonary haemodynamic response to fMLP in endotoxin primed rats. Issue 1 (23rd December 2003) - Song, C; Suzuki, S; Kubo, H; Chida, M; Hoshikawa, Y; Tabata, T; Kondo, T
Abstract : Background: The interaction between neutrophils and platelets may be important in the modulation of pulmonary haemodynamics under systemic inflammatory conditions. A study was undertaken to examine whether antiplatelet agents inhibit platelet-neutrophil adherence and ameliorate the pulmonary haemodynamic response to fMLP by inhibiting thromboxane release in endotoxin primed lungs. fMLP stimulates neutrophils but not platelets; however, thromboxane synthesis in neutrophils is very low. Methods: Rats were pretreated with either cilostazol (300 mg/kg) or aspirin (50 mg/kg) before endotoxin priming (5 mg/kg). Platelets in the lung were identified by fluorescent immunohistochemistry. Platelet-neutrophil adherence was analysed by flow cytometry of the lung vascular flush. The effect of fMLP (10 −6 M) on thromboxane release, lung weight (an indicator of pulmonary vasoconstriction), and lung filtration coefficient was determined in an isolated lung system perfused at a constant pressure difference. Results: Endotoxin induced platelet accumulation and platelet-neutrophil adherence in the lung capillary were completely inhibited by cilostazol and aspirin while neutrophil recruitment was not affected. The fMLP challenge caused a significant increase in thromboxane B2 levels in endotoxin primed lungs. The fMLP induced decrease in lung weight was enhanced by endotoxin priming (from −4.9 to −63.9 mg, 95% CI of mean difference −99.5 to −10.5 mg, p<0.05). The fMLP induced increase in the lung filtration coefficient was also enhanced by endotoxin priming (from 0.63 to 2.40 mg/min/cm H2 O/g, 95% CI of mean difference 1.17 to 2.37 mg/min/cm H2 O/g, p<0.05). Treatment with cilostazol and aspirin completely inhibited the enhanced pulmonary haemodynamic response to fMLP. Conclusion: The neutrophil–platelet interaction is of critical importance in the modulation of pulmonary haemodynamics via thromboxane.